Jejak Hasil Peninggalan Budaya Manusia Prasejarah di Song Terus Pacitan - sri dwi Ratnasari (Jurnal CULTURE (Culture, Language, and Literature Review), 2015)
Pacitan with the title "Capital of Prehistory" has a lot of sites that are a reflection of prehistoric life. Song Terus wich is one of sites, the located in the village of Wereng, Punung, Pacitan. Song Terus a series of Thousand Mountains stretching from Yogyakarta, Wonosari, Wonogiri and Pacitan. This research aims (1), to determine the general picture Song Terus, (2) To determine the findings associated with prehistoric sites in Song Terus and (3) to determine prehistoric human cultural heritage trail in Song Terus. This study used a qualitative descriptive study using the approach of the writing of history (historical). The results showed that Song Terus is a prehistoric site that reflects the picture of prehistoric human life. Song Terus as cave prehistoric human settlements, with the discovery of relics result of the findings of human fossils, animal fossil and the results of human culture. The first human fossils were found including Australomelanesid race. One of the human fossils is called the "Mbah Sayem" which is regarded as the oldest man in the village of Wereng. Animal fossil found are many types of monkeys, buffalo, cows, birds, reptiles, deer and antelope. Results of human culture in the form of artifacts constitute the equipment of prehistoric human fulfillment that comes from rocks and animal bones. Artifacts such as kapak genggam, kapak perimbas, serpih, flakes, and alat tulang. Activity of a society that is still moving, grouping and division of tasks between them is reflected in the cultural relics and remains of fauna show that the Song Terus a residential sites Palaeolithic (Old Stone period).  Keywords: Prehistoric Culture, Song Terus, Paleolithic